Converting fruit waste into carbon dots for bioimaging applications. (June 2022) - Kaur, P.; Verma, G.
Abstract: Carbon dots (CDs) are 0-D nanomaterials with unique structural and optical properties. Compared to fluorescent organic agents or semiconductor quantum dots, CDs offer several advantages such as higher photostability, lower toxicity, better biocompatibility, easier synthesis, and surface modifications. This endows CDs with immense potential to serve many applications like photocatalysis, biosensing, bioimaging, drug delivery, memory devices, etc. Fruit waste is a perfect choice to synthesize CDs as it is compositionally rich, easily available, renewable, and sustainable. It also caters well to the ongoing research interests of the scientific community to use environmental waste for advanced technologies. Modern solutions for fruit waste handling are urgently needed as the conventional methods are just not sufficient to realize the full potential of treasured fruit parts, which are otherwise termed as 'waste'. In this scenario, the present review article is dedicated to understanding the conversion of fruit waste into CDs for bioimaging applications. It discusses feasibilities and superiorities of adopting fruit waste as carbon source, merits and demerits of synthesis, bioimaging techniques, morphology, and optical properties of CDs. Some other major factors, which affect the fluorescence emission of CDs, such as dopants, chemical composition, hydrophilicity, surface-passivation, defects, etc., are analyzed too. The article concludes with a discussion of challenges and future perspectives of fruit waste-derived CDs for wider implications. Graphical abstract: Image 1